Complementary Specializations of the Left and Right Sides of the Honeybee Brain - Rogers, Lesley J.; Vallortigara, Giorgio (Frontiers in Psychology, 2019)
Honeybees show lateral asymmetry in both learning about odors associated with reward and recalling memory of these associations. We have extended this research to show that bees exhibit lateral biases in their initial response to odors: viz., turning toward the source of an odor presented on their right side and turning away from it when presented on their left side. The odors we presented were the main component of the alarm pheromone, isoamyl acetate (IAA), and four floral scents. The significant bias to turn toward IAA odor on the right and away from it on the left is, we argue, a lateralization of the fight-flight response elicited by this pheromone. It contrasts to an absence of any asymmetry in the turning response to an odor of the flowers on which the bees had been feeding prior to testing: to this odor they turned toward when it was presented on either the left or right side. Lemon and orange odors were responded to differently on the left and right sides (toward on the right, away on the left), but no asymmetry was found in responses to rose odor. Our results show that side biases are present even in the initial, orienting response of bees to certain odors.